Stomach Content Analysis of Mytus nemurus C.V from the Banjiran Swamp, Air Hitam River, Payung Sekaki District, Riau Province - Siregar, Rida Amaliah; Putra, Ridwan Manda; Efizon, Deni (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbstractMystus nemurus C.V is one of freshwater fish that inhabit the Banjiran swamps. To understand the type of food consumed by M. nemurus, a study has been conducted on February - March 2018. There were 100 fishes captured, that was consisted of 71 fishes with filled stomach and 29 fishes with empty stomach. Stomach content of the fish was analyzed as a basis to calculate the Preponderance Index (PI). Results shown that the main food of M. nemurus was fish (38%), the complementary food was unidentified debris (31%), and additional food was plant (24%), insects (4%), crustacean (1%), and domestic waste (2%). Keywords: Catfish, fish food, Index of Preponderance, Flooded Area